A study on information governance in Universiti Teknologi MARA (UiTM) Pahang branch / Nur Fatihah Muhamad - Muhamad, Nur Fatihah (Universiti Teknologi MARA, 2021)
Information is vital as it enables people perform their works properly and effectively. In higher education institutions, there have a lot of information that need to be governed and managed systematically in which in turn it will ensure that employees can utilize it effectively for daily operations. Information governance is a basis of management policy designed to reduce the risks, to stabilize the cost involved in the organization and also corporate governance. It also involves information quality, information value, information security, information privacy and organizational context. Information quality will give the benefit to the top management to ensure that they make a good decision and proper action. While, information value will give a satisfaction to the users because the information could be used deepest and longest. Information security and information privacy are useful to ensure the information is keep safely and cannot freely spread to the users which will affect the institution. Besides that, the organizational context is the organizational characteristics such as its strategies, policies, structures and cultures in the institutions. Despite of these facts, there is little research that investigates into information governance in higher education institution is being made. The aim of this research is to examine the implementation of information governance in UiTM Pahang Branch. The top management in the institution needs the proper records to make the decision besides it also can reduce risks and cost by employed various technologies and activities while social media also can be used to spread the information to the users. Based on the correlation analysis that has been made to test the hypothesis, it has been proved that there has a positive status of the information governance implementation in UiTM Pahang Branch.